Economics - Economics of Proration (With Discussion) - Joseph E. Pogue (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
Proration in the petroleum industry has come to mean a method for curtailing the production of crude petroleum by artificial effort, and it is in this sense that the term is employed throughout this paper. Although a contrived curb on supply has been invoked at various times in the past in particular fields and to meet specific situations, it is not until the past few years that this procedure has become general and assumed a dominant role in the oil business. In the sense that we now understand it, proration had its inception in the Seminole area of Oklahoma in 1927, from which time and place the practice spread to include practically all the flush oil fields of the country, especially those of California, Kansas, Oklahoma and Texas. At present there is perhaps no phase of the oil business that commands more attention than proration, nor one that engages more time and effort on the part of executives in the business. The practice of proration, indeed, has not only become an integral part of the policy of most companies and operators, but it has also taken on the aspects of a "movement" involving two schools of thought with considerable feeling, and at times some bitterness, on both sides. In this atmosphere it is difficult to find calm, dispassionate consideration of proration, for most discussions are either vigorous exhortations by its proponents, or else sharp condemnations by its opponents; although it appears that the majority of the industry is clearly "in favor of" proration. It is hoped that this analysis will be taken as an attempt to appraise the movement as an economic force, without bias and without regard to the incidence of the conclusions upon any preconceptions that the industry may entertain. Evolution of Proration To appreciate the causes that brought proration into being, it is necessary to view briefly the development of the petroleum industry over the past twenty years, approximately the span of the gasoline era., For the first ten years of the period, the industry was seeking capital